Stable patients and patients with advanced disease: consensus definitions to support sustained scale up of antiretroviral therapy. Issue 9 (22nd July 2016) - Waldrop, Greer; Doherty, Meg; Vitoria, Marco; Ford, Nathan
Abstract: Objective: As guidelines are evolving towards recommending starting antiretroviral therapy (ART) in all HIV‐positive individuals irrespective of clinical and immunological status, HIV programmes will be challenged to manage an increasingly diverse set of patient needs. To support global guideline recommendations for differentiated service delivery, WHO developed consensus definitions for two distinct patient populations: patients presenting with advanced disease and patients who are stable on ART. Methods: An expert panel consisting of 73 respondents from 28 countries across all six WHO regions supported the development of these definitions. The panel included clinicians, researchers, programme managers, technical advisors and patient group representatives. Results: Patients presenting with advanced disease at presentation to care were defined as CD4 count <200 CD4 cells/mm 3 or WHO Stage III & IV defining illness. Patients stable on ART were defined as those who were receiving ART for at least 1 year with no adverse drug reactions requiring regular monitoring, no current illnesses or pregnancy, a good understanding of lifelong adherence, and evidence of treatment success. Treatment success was defined as two consecutive undetectable viral load measures or, in the absence of viral load monitoring, rising CD4 counts or CD4 counts above 200 cells/mm 3 and an objective adherence measure. Conclusions: Patients who are stable on ART should be offered a less intensive care package that can lead to improved outcomes while saving resources, including less frequent clinic visits, out‐of‐clinic drug refills and reduced laboratory monitoring. This will allow for clinic resources to be directed towards reducing morbidity and mortality among patients presenting with advanced disease.